Hubungan Dakwah Dengan Ahli Korporat - Mohd Zin, Ab. Aziz (Jurnal Usuluddin, 2000)
The article discusses the rapid development of da'wah throughout the world in the early days. The evidence has shown that da'wah was strongly supported by the corporate sectors. It means, in the early da'wah, the corporates played a very important role. Thus, it could be established that the relationship between the two parties was very close.